Islamic Law and the Constitution: Analyzing the Compatibility of Religion-Based Legislation in Indonesia - Hadi Iskandar; Yusrizal Hasbi; Zahratul Idami; Ferdy Saputra (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2025)
This study explores the constitutional compatibility of religion-based legislation in Indonesia, particularly laws influenced by Islamic jurisprudence, within the framework of the 1945 Constitution. As a Muslim-majority nation that embraces both religious values and democratic pluralism, Indonesia faces ongoing tensions between the demands for the formalization of Islamic norms and the constitutional commitment to human rights, legal equality, and religious freedom. The expansion of Sharia-inspired by laws at the regional level and Islamic influences in national statutes underscore the urgency of addressing this legal-religious interplay. While existing scholarship has addressed the sociopolitical and administrative aspects of religion-based lawmaking, there remains a lack of doctrinal analysis focused on constitutional alignment. This study employs a legal research method, which focuses on the analysis of legal norms, statutory regulations, and constitutional principles as textual constructs. This research fills that gap by applying a juridical-doctrinal approach to evaluate whether such legislation adheres to principles enshrined in the Constitution, including legal certainty, non-discrimination, and constitutional supremacy. Through critical analysis of legislation and Constitutional Court decisions, the study demonstrates that while certain religious laws can coexist with Pancasila and constitutional values, many pose substantive challenges to Indonesia’s legal order. The findings contribute to broader debates on legal pluralism, constitutionalism, and the appropriate role of religion in legislation, offering normative guidance for aligning religious norms with democratic constitutional principles.